DEVELOPMENT OF A STEM-BASED E-MODULE ON NATURAL COLORANT ICE CREAM FROM SAPPAN WOOD (CAESALPINIA SAPPAN (L.)) FOR STRENGTHENING THE PANCASILA STUDENT PROFILE - Seritami, Seritami; Hadiarti, Dini; Kurniasih, Dedeh (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop an innovative e-learning module focused on STEM education, leveraging the research potential of Caesalpinia sappan L. extract as a natural dye in ice cream production. The module is integrated into the Pancasila Student Profile Strengthening Project (P5) for senior high school students, enhancing understanding of STEM concepts while promoting sustainability and cultural relevance. The research employs the ADDIE development framework, consisting of Analysis, Design, Development, Implementation, and Evaluation stages, alongside the Research and Development (R&D) method. Nine subject matter, media, and language specialists validated the module. Data analysis used a descriptive quantitative approach, with validity assessed via expert validation sheets and practicality evaluated through student response questionnaires. The e-module scored high in validation, with 95.02% for content, 88.14% for media, and 93.96% for language, indicating strong validity. Practicality assessments were conducted in two parts, with a mini-experiment involving 12 students yielding a rating of 79.06% and a larger trial with 60 students achieving 80.35%, both deemed practical. The results position the e-module as valid, beneficial, and applicable for contextual, project-based education highlighting West Kalimantan's local potential.